Artificial Intelligence (AI) and Copyright Law in Nepal: Bridging Legal Gaps in the Digital Era - Aryal, Giri Raj (Far Western Journal of Education, 2025)
This study examines the adaptation of copyright law to emerging technologies, with a focus on artificial intelligence (AI) and digital platforms in Nepal. It explores the Nepalese Copyright Act of 2002, identifying its inadequacies in addressing AI-generated t content and online piracy. Using a comparative legal approach, the research contrasts Nepal’s framework with international standards, such as the Berne Convention and the WIPO Copyright Treaty. Findings reveal that Nepal’s legislation lacks provisions for AI-generated works, resulting in ambiguities in authorship and ownership due to the non-human nature of AI. Global approaches vary, with countries like the UK and China adopting different models, highlighting the need for harmonized standards. Nepal’s enforcement is hindered by limited resources and outdated systems, exacerbating challenges in protecting creators from digital infringement. The study recommends i amending the Copyright Act to define authorship for AI works, strengthen anti-piracy measures, and align with global best practices. Proposed measures include implementing notice-and-takedown procedures, enhancing enforcement mechanisms, and increasing public awareness to balance creator rights with innovation. These reforms aim to reinforce Nepal’s copyright system, ensuring it supports a competitive digital economy while promoting equitable access to knowledge and fostering innovation on a global scale.